Plan de marketing para la empresa entorno cultural del Ecuador en la ciudad de Quevedo año 2011 - Cuacés Navarrete, Fanny Narcisa (2012)
Cultural Environment of Ecuador, a service company for sale of books in the city of Quevedo, his philosophy is to bring culture to the Ecuadorian households throughout the book provide ease so they can acquire at least two books a year. To remain competitive in the market was obliged to make changes in management and company policies why a research conducted on the level of reading Quevedo, and an analysis of sales of the company, to develop the marketing plan proposal. In the research to assess the reading level Quevedo took the world population by level of education of 46,815 inhabitants, was applied to a sample survey of 381 people of which 81% correspond to 309 high school students and 29% correspond to 72 college students. For this survey were selected educational institutions more representative of Quevedo, schools Eloy Alfaro, Ladies Quevedo, San Camilo, Abdòn Calderon and Quevedo State Technical University according to the survey, 57% reported reading as very important and for a 19% extremely important showing growing interest in reading Quevedeña youth representing a potential market. 42% also buy more than three books a year, and 34% bought two a good result for the parameters of the company that handles sales For the analysis of the decline in sales of the company compared the monthly sales reports for the last three years where it is contemplated that sales have been declining gradually to reach 37.5% at present, we also observed that the variable new client intake has decreased 37.3%, of which only 52% made their second order, women representing 80% of total enterprise customers including 92% are mothers. With the results of research on the level of reading and analysis of the sales decline the proposal was developed marketing plan. Which was made with solid ideas, well defined and shaped by the objectives, fulfilling the characteristics of a good plan, complete, well organized, understandable and effective? In the first instance there was a full diagnosis of the company, its environment, competition, target market was determined, with the market segment where you want to go with bids, continued with the SWOT analysis was established plan objectives which is to improve profitability and positioning the company in the market, created the corporate image, then performed the services marketing mix with all its elements, we defined the timing of promotions, the budget and control plan marketing.